Development of life skills: the SUPREM program (Training and Practice : Journal of Educational Sciences, 2023)
The study focuses on the necessity and the opportunities to develop general life skills related to teenagers' career choices and coping with everyday challenges. The aim is to present the intellectual outputs developed in the framework of the international education development project Successful Preparation Model for Schools (SUPREM), supported by Erasmus+. In this way, it wants to contribute to supporting teachers, parents and students in public education in the period of career choice, in making successful decisions, in choosing pathways to further education according to individual abilities, and in encouraging active involvement in the lifelong learning process.
Keywords: career guidance; life skills; lifelong learning; primary school students